Study on the Effects of Gamma Irradiation on Protocorm-Like Bodies of Dendrobium Hybrid against Fusarium proliferatum and Fusarium oxysporum - Sangeetha Siva Sangu; Nik Mohd Izham Mohamed Nor; Latiffah Zakaria; Azhar Mohamad; Sreeramanan Subramaniam (Tropical Life Sciences Research, 2019)
Dendrobiums orchids are prone to diseases caused by Fusarium proliferatum and Fusarium oxysporum. Therefore, gamma irradiation was utilised on Dendrobium hybrid, D5 to produce cultivars that are resistant towards these fungi. Gamma doses of 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 Gray (Gy) were radiated on thin cell layer (TCL) of protocorm-like bodies (PLB) and were observed for four weeks. Gamma doses of 20 and 30 Gy were optimum for survivability and shoot regeneration of treated PLB. The radio sensitivity (LD50) of the PLB was approximately 63 Gy. Histology and scanning electron microscopy (SEM) analysis showed prominent cell damage and alteration in surface morphology in gamma irradiated PLB. The number of stomata and stomatal aperture decreased where it was 15.47 ± 8.16 µm at 10 Gy but reduced to only 8.24 ± 3.91 µm at 90 Gy. Direct amplification of minisatellite DNA (DAMD) showed high degree of polymorphism in these PLB. When challenged with spore suspension of these fungi, plantlets radiated with 20 and 30 Gy of gamma irradiation showed the least disease symptom, thus, proving resistance towards these fungi. Therefore, this study is a preliminary screening study where the optimum doses of gamma irradiation were selected based on the reaction of radiated TCL of PLB towards the mutagen. Dendrobium orkid mudah terdedah kepada penyakit yang disebabkan oleh Fusarium proliferatum dan Fusarium oxysporum. Oleh itu, penyinaran gamma digunakan pada hibrid Dendrobium, D5 untuk menghasilkan kultivar yang tahan terhadap kulat ini. Dos gamma 10, 20, 30, 40, 50, 60, 70, 80, 90 dan 100 Grey (Gy) dipancarkan pada lapisan sel nipis (TCL) badan seperti protocorm (PLB) dan diperhatikan selama empat minggu. Dos gamma 20 dan 30 Gy adalah optimum untuk kelangsungan hidup dan penjanaan semula pucuk PLB yang dirawat. Sensiviti radio (LD50) PLB adalah kira-kira 63 Gy. Analisis histologi dan pemeriksaan mikroskop elektron (SEM) menunjukkan kerosakan sel yang utama dan perubahan dalam morfologi permukaan dalam PLB yang menyinari gamma. Bilangan stomata dan stomatal aperture menurun di mana ia adalah 15.47 ± 8.16 ?m pada 10 Gy tetapi dikurangkan kepada hanya 8.24 ± 3.91 ?m pada 90 Gy. Penguatan langsung DNA minisatelit (DAMD) menunjukkan tahap polimorfisme yang tinggi dalam PLB ini. Apabila dicabar dengan penggantungan spora kulat ini, kilang-kilang yang dipancarkan dengan 20 dan 30 Gy penyinaran gamma menunjukkan gejala penyakit yang paling kurang, oleh itu, membuktikan ketahanan terhadap kulat ini. Oleh itu, kajian ini adalah kajian saringan awal di mana dos optimum penyinaran gamma dipilih berdasarkan tindak balas TCL yang dipancarkan PLB terhadap mutagen.